2014
DOI: 10.1007/s00228-014-1671-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel drug targets in clinical development for heart failure

Abstract: Clinical trials in heart failure must be designed to minimize the risk of "drug failures." Nevertheless, it is hoped that in the days to come, drugs with superior efficacy and safety will eventually be produced from the surge of molecules that are in the pipeline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…The development of CVD results from various impairments, including cardiomyocyte apoptosis, cardiac remodeling and hypertrophy in cardiac function (George et al, 2014;Fujita and Ishikawa, 2011). It was also suggested that cardiac oxidative stress, inflammation and fibrosis played a vital role in the development of CVD (Butts et al, 2015;Weldy et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The development of CVD results from various impairments, including cardiomyocyte apoptosis, cardiac remodeling and hypertrophy in cardiac function (George et al, 2014;Fujita and Ishikawa, 2011). It was also suggested that cardiac oxidative stress, inflammation and fibrosis played a vital role in the development of CVD (Butts et al, 2015;Weldy et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…11 For this reason, SERCA2a has been a focal point for the development of an improved range of inotropic drugs. Pharmaceutical agents, such as the Na + /K + ATPase inhibitor istaroxime, that increase SERCA activity have been tested with some positive outcomes in experimental and clinical studies, 16 but such agents have other actions that may present problems. Another approach is to reverse the lowered SERCA expression level directly by gene therapy, and considerable effort has been made in this regard.…”
Section: Serca2amentioning
confidence: 99%
“…2). A number of currently used inotropic drugs act by increasing cAMP levels and thereby activating PKA, leading to increased PLN S 16 phosphorylation by pln in healthy heart under basal conditions, stimulated conditions, and in heart failure. a positive inotropic stimulus increases phosphorylation and dysinhibits serCa2a.…”
Section: Phospholamban Phosphorylationmentioning
confidence: 99%
See 2 more Smart Citations